Relationships between arterial stiffness and the cluster of cardiovascular disease risk factors - Sataman, Sarinda; Pipatkasira, Pornsiri; Phuegsilp, Pornpiroon; Saelao, Benjawan; Pisalayon, Thanwalai; Nualnim, Nantinee (Archives of Allied Health Sciences, 2025)
Evidence indicated that individuals with more than one cardiovascular disease (CVD) risk factor were more likely to develop CVD events, compared with those with a single risk factor. Arterial stiffness is known as an independent risk factor for CVD. This study aimed to explore the association of clustering of CVD risk factors and arterial stiffness. Arterial stiffness was measured in both male and female adults aged 49.04 ± 15.79 years who visited the vascular screening clinic at the Physical Therapy Center, Mahidol University. Participants with two or more risk factors were assigned to the cluster of CVD risk factors group. This study was part of a routine-to-research (R2R) project; therefore, all participants who were willing to receive the service from September 2021 to April 2023 were recruited into the study with their permission. The results showed that the brachial-ankle pulse wave velocity (baPWV), an arterial stiffness indicator, was highest in the clustering of CVD risk factors group (1594 cm/sec2), higher in the single CVD risk factor group (1263cm/sec2) than in none of CVD risk factors participant (1148 cm/sec2). The overall mean resting mean arterial blood pressure level was 90 mmHg. In conclusion, clustering of CVD risk factors significantly correlated with arterial stiffness. Lifestyle modification should be strongly encouraged for individuals with more than one CVD risk factor to reduce the burden of CVD.